ANALISIS KEBIJAKAN ALOKASI ASET, KINERJA MANAJER INVESTASI DAN TINGKAT RISIKO TERHADAP KINERJA REKSADANA SAHAM DI INDONESIA - Sari, Anindita Putri Nurmalita; Purwanto, Agus (Diponegoro Journal of Accounting, 2012)
Mutual fund are used to collect funds from public investors to be invested in portfolio securities by investment manager who has license from Bapepam-LK. Each year the number of equity mutual fund investment increased, but its not equal to the number of investors who investing in equity mutual fund. This is because a lack of knowledge of performance indicators equity mutual fund, the selection of mutual fund that give optimal results and measure the performance of mutual fund shares with Sharpe Ratio. This research aims to analyze the performance of equity mutual funds in Indonesia that be affected by asset allocation policy, the ability of investment managers in stock selection and market timing, and also the level of risk. The research uses pooling data method. The data used in the form of an active equity mutual fund during the period January 2007-December 2011 annual total of 15 mutual funds with a total of 75 data items. The method used to calculate the performance of equity mutual fund is Sharpe Ratio. The method used in this study were multiple regression and classic assumptions of normality test, multicollinierity test, autocorrelation test and heteroskesdatisity test. F test and T test used to hypotheisi test. These result indicate that the asset allocation policy has negatif and not significan effect on the equity mutual fund performance. The performance of investment manager has positive and significant effect on the performance of equity mutual fund. And risk level has negative and significant effect on the performance of equity mutual fund.